Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

First substantial evidence for Old World vultures (Aegypiinae, Accipitridae) from the early Palaeolithic and Iberomaurusian of Morocco - Albrecht Manegold; Rainer Hutterer (PalZ, 2021)
Remains of at least three species of large aegypiine vultures from early Palaeolithic and Iberomaurusian of Ifri n’Ammar, Morocco are the first substantial fossil record of these taxa in the Maghreb. They can be tentatively referred to the two extant species Aegypius monachus (Cinereous Vulture) and Gyps fulvus (Griffon Vulture), and to the extinct Gyps melitensis . Few fragments of remarkably large bones may belong to especially large specimens of A. monachus , but it cannot be ruled out that they are indeed remains of the so far only insufficiently known palaeospecies A. prepyrenaicus Hérnandez, 2001, originally described from the Upper Pleistocene of Spain. Two vulture species definitely occurred contemporarily; Gyps fulvus was found in the entire sequence, while A. monachus occurred only between 13,800 and 17,000 calBP. G. melitensis was found only once in an unknown stratigraphic context. All remains were found along with human artefacts in a cave deposit. Few bones show longitudinal scratches, which probably are cut marks, indicating that humans made use of the flesh, feathers and/or bones of these vultures. None of these species were previously recorded for the Upper Pleistocene of the Maghreb, and the fossil specimens provide important evidence for the former distribution of Old-World vultures in this area, which is insufficiently known and which changed dramatically during the twentieth century.

Multilocus phylogeny of the Crocidura poensis species complex (Mammalia, Eulipotyphla): Influences of the palaeoclimate on its diversification and evolution - Violaine Nicolas; François Jacquet; Rainer Hutterer; Adam Konečný; Stephane Kan Kouassi; Lies Durnez; Aude Lalis; Marc Colyn; Christiane Denys (Journal of Biogeography, 2019)
Aim This study aims to reconstruct the evolutionary history of the Crocidura poensis species complex and to identify factors driving diversification within it. We tested whether: (a) there is a pattern of allopatric differentiation coincident with the location of hypothesized Pleistocene forest refugia, (b) sister taxa are separated by broad rivers, (c) sister taxa occupy adjacent but distinct habitat. Location Sub‐Saharan African forests and adjacent savanna. Taxon Shrews. Methods Analyses were based on 247 specimens collected from across the distribution of the species complex. We reconstructed the phylogeny (Bayesian and maximum likelihood methods) and assessed historical biogeography of this taxonomic group using a combination of mitochondrial and nuclear markers. We mapped the genetic diversity and estimated the divergence times by a relaxed clock model. Informed by multilocus species delimitation methods, we discussed possible taxonomic implications. Results This complex is composed of nine major genetic lineages (proposed species). The earliest split within this complex occurred after 2.0–2.4 Ma, which corresponds to a period of increased aridity and/or extreme environmental variability. Most other divergence events occurred after the Early‐Middle Pleistocene Transition (1.2–0.8 Ma). Divergent selection across ecological gradients could explain diversification within the West African lineage. In Central Africa, the observed phylogeographic pattern fits the Pleistocene refuge hypothesis and supports the existence of multiple small rather than a few large forest refugia during glacial maxima. Large rivers, like the Congo and Sanaga Rivers, are important barriers to gene flow for several lineages but probably were not the primary cause of differentiation. Main conclusions Both geographic isolation in distinct forest refugia and divergent selection along ecological gradients could explain Pleistocene diversification within this complex.

Testing heterogeneous base composition as potential cause for conflicting phylogenetic signal between mitochondrial and nuclear DNA in the land snail genus Theba Risso 1826 (Gastropoda: Stylommatophora: Helicoidea) - Andre Böckers; Carola Greve; Rainer Hutterer; Bernhard Misof; Martin Haase (Organisms Diversity & Evolution, 2016)

Forest refugia and riverine barriers promote diversification in the W est A frican pygmy shrew ( C rocidura obscurior complex, S oricomorpha) - François Jacquet; Violaine Nicolas; Marc Colyn; Blaise Kadjo; Rainer Hutterer; Jan Decher; Bertin Akpatou; Corinne Cruaud; Christiane Denys (Zoologica Scripta, 2014)
The Crocidura obscurior or West African pygmy shrew complex is endemic to West African forests from south‐eastern Guinea, eastern Liberia, southern Côte d'Ivoire and south‐western Ghana. We explore the genetic and morphometric diversity of 239 individuals of the C. obscurior complex from 17 localities across its geographical range. Using genetic data from three mitochondrial (16S, cytochrome b and COI ) and four nuclear markers ( BRCA 1, STAT 5A, HDAC 2 and RIOK 3) and skull geometric morphometrics, we show that this complex is composed of two cryptic and sympatric species, C. obscurior and C. eburnea . We then test several hypotheses to infer their evolutionary history. The observed phylogeographical pattern based on cytochrome b and COI sequences fits the forest refuge theory: during arid phases of the Plio‐Pleistocene, around 3.5, 2.1, 1 and 0.5 Mya, a small number of populations survived in isolated forest patches and diverged allopatrically. During wetter climatic periods, forests expanded, leading to secondary contacts between previously isolated populations. Our results also suggest the possible contribution of episodes of isolation in subrefuges. Historical variation of the West African hydrographic network could also have contributed to the observed patterns of genetic differentiation. Rivers such as the Volta and Sassandra may act as past and/or current barriers to gene flow. Although these two species have sympatric distributions, their phylogeographical histories are somewhat dissimilar due to small differences in their dispersal abilities and ecological requirements.

Phylogeography of an invasive land snail: natural range expansion versus anthropogenic dispersal in Theba pisana pisana - Carolin Däumer; Carola Greve; Rainer Hutterer; Bernhard Misof; Martin Haase (Biological Invasions, 2012)

Systematics and diversification of Praomys species (Rodentia: Muridae) endemic to the Cameroon Volcanic Line (West Central Africa) - Alain D. Missoup; Violaine Nicolas; Wim Wendelen; Ernest Keming; Charles F. Bilong Bilong; Arnaud Couloux; Ekobo Atanga; Rainer Hutterer; Christiane Denys (Zoologica Scripta, 2012)
Missoup, A.D., Nicolas, V., Wendelen, W., Keming, E., Bilong Bilong, C.F., Couloux, A., Atanga, E., Hutterer, R. & Denys, C. (2012). Systematics and diversification of Praomys species (Rodentia: Muridae) endemic to the Cameroon Volcanic Line (West Central Africa). — Zoologica Scripta , 41 , 327–345. Our integrative approach combines two mitochondrial genes (16S and cyt b gene), two nuclear genes (exon 10 GHR and exon 1 IRBP) and craniometrical data to test the status and to infer phylogenetic relationships of the three Praomys Cameroon Volcanic Line endemics ( P. hartwigi , P. morio and P. obscurus ). The taxonomic rank of the principal genus group is assessed and the mode of diversification of species of the P. tullbergi complex in Afrotropical forests is discussed based on estimates of times to the most recent common ancestors and on tree topologies. This study documents for the first time the molecular and morphometrical distinctiveness of P. hartwigi and P. morio within the P. tullbergi species complex. Further studies including specimens of P. hartwigi from all its distribution range are needed to conclude on the status of P. obscurus . The monophyly of the genus Praomys is refuted. Times to the most recent common ancestors of major clades within the P. tullbergi species complex are estimated for the last 2.5 Mya and during the last 1 or 2 Mya for different species or forms. The lowland forest refuge hypothesis might well explain the diversification of P. misonnei , P. rostratus and P. tullbergi in the guineo‐congolese forest block. The isolation of montane forests could have facilitated the divergence between the two montane forest forms P. hartwigi and P. obscurus and between populations of P. morio from the continent and those from the island of Bioko. Praomys populations (species) that inhabit the Cameroon Volcanic Line Praomys probably originated as lowland forms subsequently specialized to highland conditions.

Diet of the extinct Lava mouse Malpaisomys insularis from the Canary Islands: insights from dental microwear - Cyril Firmat; Helder Gomes Rodrigues; Rainer Hutterer; Juan Carlos Rando; Josep Antoni Alcover; Jacques Michaux (The Science of Nature, 2011)

Evolution of an invasive rodent on an archipelago as revealed by molar shape analysis: the house mouse in the Canary Islands - Jacques Michaux; Thomas Cucchi; Sabrina Renaud; Francisco Garcia‐Talavera; Rainer Hutterer (Journal of Biogeography, 2007)
Aim The aim of this paper is to identify the patterns in the morphological differentiation in Canary Island mice, based on fossil and modern samples. In order to achieve this, the mouse species present on the archipelago were first compared with a set of continental mice. The differences between the continental and Canary Island samples, and among the Canary Island samples, provide insights into the processes of colonization and the subsequent insular evolution. Location Canary archipelago. Methods An outline analysis based on Fourier transformation was used to quantify shape differences between lower molars. Together with the fossil and modern Canary Island samples, a reference set of genotyped continental populations of the commensal Mus musculus and the wild Mus spretus was used for comparison. Results The morphometric analysis showed that all the mouse specimens from the Canary Islands and Cape Verde belonged to Mus musculus domesticus. Lower molars of extant mice from La Gomera, El Hierro, Gran Canaria, Tenerife, and to a lesser degree from Lanzarote, were similar to those of genotyped M. m. domesticus from the continent, while teeth of extant mice from Fuerteventura were more divergent. Fossil mice from Fuerteventura were very similar to the extant representatives on this island, and similar to the fossil mice on the nearby islands of Lobos and La Graciosa. Main conclusions The mouse present on the Canary archipelago has been identified as the house mouse M. m. domesticus . Based on the shape of the lower molar, the Canary Island mice are divergent from the continental ones, but the degree of divergence varies with the geography of the archipelago. Overall, populations from eastern islands are more divergent from the continental mice than populations from western ones. Fossil populations indicate that this situation was established several centuries ago. Two main factors may have contributed to this pattern: the appearance of different types of environment on the islands since the successful settlement of the mouse, and/or the number of subsequent introductions of continental individuals via shipping.

Phylogeographical footprints of the Strait of Gibraltar and Quaternary climatic fluctuations in the western Mediterranean: a case study with the greater white‐toothed shrew, Crocidura russula (Mammalia: Soricidae) - JEAN‐FRANÇOIS COSSON; RAINER HUTTERER; ROLAND LIBOIS; MAURIZIO SARÀ; PIERRE TABERLET; PETER VOGEL (Molecular Ecology, 2005)
We used mitochondrial cyt b sequences to investigate the phylogenetic relationships of Crocidura russula ( sensu lato ) populations across the Strait of Gibraltar, western Europe, Maghreb, and the Mediterranean and Atlantic islands. This revealed very low genetic divergence between European and Moroccan populations. The application of a molecular clock previously calibrated for shrews suggested that the separation of European from Moroccan lineages occurred less than 60 000 bp , which is at least 5 million years (Myr) after the reopening of the Strait of Gibraltar. This means that an overwater dispersal event was responsible for the observed phylogeographical structure. In contrast, genetic analyses revealed that Moroccan populations were highly distinct from Tunisian ones. According to the molecular clock, these populations separated about 2.2 million years ago (Ma), a time marked by sharp alternations of dry and humid climates in the Maghreb. The populations of the Mediterranean islands Ibiza, Pantelleria, and Sardinia were founded from Tunisian populations by overwater dispersal. In conclusion, overwater dispersal across the Strait of Gibraltar, probably assisted by humans, is possible for small terrestrial vertebrates. Moreover, as in Europe, Quaternary climatic fluctuations had a major effect on the phylogeographical structure of the Maghreb biota.